Sustainable Development in Science Policy-Making : The German Federal Ministry of Education and Research's Policies for International Cooperation in Sustainability Research /: The German Federal Ministry of Education and Research's Policies for International Cooperation in Sustainability Research. (2019) - Schwachula, Anna
No abstract available